Long chain polyunsaturated fatty acid supplementation in infant formula and blood pressure in later childhood: follow up of a randomised controlled trial. Issue 7396 (3rd May 2003) - Forsyth, J S; Willatts, P; Agostoni, C; Bissenden, J; Casaer, P; Boehm, G
Abstract: Objective: To determine whether supplementation of infant formula milk with long chain polyunsaturated fatty acids (LCPUFAs) influences blood pressure in later childhood. Design: Follow up of a multicentre, randomised controlled trial. Setting: Four study centres in Europe. Participants: 147 formula fed children, with a reference group of 88 breastfed children. Intervention: In the original trial newborn infants were randomised to be fed with a formula supplemented with LCPUFAs (n=111) or a formula without LCPUFAs but otherwise nutritionally similar (n=126). In the present follow up study the blood pressure of the children at age 6 years was measured. Main outcome measures: Systolic, diastolic, and mean blood pressure. Results: 71 children in the LCPUFA supplementation group (64% of the original group) and 76 children in the non-supplementation group (60%) were enrolled into the follow up study. The LCPUFA group had significantly lower mean blood pressure (mean difference −3.0 mm Hg (95% confidence interval −5.4 mm Hg to −0.5 mm Hg)) and diastolic blood pressure (mean difference −3.6 mm Hg (−6.5 mm Hg to −0.6 mm Hg)) than the non-supplementation group. The diastolic pressure of the breastfed children (n=88 (63%)) was significantly lower than that of the non-supplemented formula group but did not differ from the LCPUFA formula group. Conclusions: Dietary supplementation with LCPUFAs during infancy is associated with lower blood pressure in later childhood. Blood pressure tends to track from childhood into adult life, so early exposure to dietary LCPUFAs may reduce cardiovascular risk in adulthood.